Enhanced fullerene–Au(111) coupling in (2√3 × 2√3)R30° superstructures with intermolecular interactions - Paßens, Michael; Waser, Rainer; Karthäuser, Silvia (Beilstein Journal of Nanotechnology, 2015)
Disordered and uniform (2√3 × 2√3)R30° superstructures of fullerenes on the Au(111) surface have been studied using scanning tunneling microscopy and spectroscopy. It is shown that the deposition and growth process of a fullerene monolayer on the Au(111) surface determine the resulting superstructure. The supply of thermal energy is of importance for the activation of a Au vacancy forming process and thus, one criterion for the selection of the respective superstructure. However, here it is depicted that a vacancy–adatom pair can be formed even at room temperature. This latter process results in C60 molecules that appear slightly more bright in scanning tunnelling microscopy images and are identified in disordered (2√3 x 2√3)R30° superstructures based on a detailed structure analysis. In addition, these slightly more bright C60 molecules form uniform (2√3 x 2√3)R30° superstructures, which exhibit intermolecular interactions, likely mediated by Au adatoms. Thus, vacancy–adatom pairs forming at room temperature directly affect the resulting C60 superstructure. Differential conductivity spectra reveal a lifting of the degeneracy of the LUMO and LUMO+1 orbitals in the uniform (2√3 x 2√3)R30° superstructure and in addition, hybrid fullerene–Au(111) surface states suggest partly covalent interactions.
Keywords: adatom–vacancy mechanism; differential conductance; fullerene; Ising model; scanning tunnelling microscopy